Dangerously informed: Voter information and pre-electoral violence in Africa. (January 2020) - von Borzyskowski, Inken; Kuhn, Patrick M
A considerable literature examines the effect of voter information on candidate strategies and voter–politician interactions in the developing world. The voter information literature argues that information can improve accountability because more informed voters are harder to woo with traditional campaign tools, such as ethnic appeals and vote-buying. However, this literature has largely ignored the reaction of political candidates and thus may reach conclusions that are overly optimistic regarding the impact of information on electoral accountability. We argue that voter information can increase electoral violence in developing countries where politicians face fewer institutional constraints on their campaign tactics. When violence is used as a campaign strategy, more informed electorates are more at risk because they are harder to sway through alternative campaign techniques. Using data from 35 African countries, we show that respondents receiving their news predominantly from newspapers are a good proxy for informed voters because they differ in terms of their political attitudes from respondents consuming no news or receiving it via other channels. Combining the geo-coded survey data with pre-electoral violence event data, we find a robust positive association between newspaper readership and fear of and exposure to campaign violence. This finding contributes to the micro-foundations of election violence and adds a cautionary note for voter information programs.